ANALISIS PENERAPAN PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN MATEMATIKA KELAS IV SD NEGERI 2 WONOKARTO - Putri Zayana, Alita; Khoiriyah, Binti; Pixyoriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of accommodating diversity learning profile of students in the Independent Curriculum through differentiated learning, Especially in mathematics subjects which are often considered abstract. This research uses a descriptive qualitative method. Purpose This research is to describe the process of implementing learning differentiated, identifying responses and impacts on students, know the obstacles faced by teachers, and formulate solutions to these obstacles in grade IV A SD Negeri 2 Wonokarto. The subject of this study is a teacher of class IV A participant educated in class IV A and principal. Data collection techniques include observation participatory, in-depth interviews with teachers, principals, and three students with different learning profiles (auditory, visual, and kinesthetic), questionnaires, and documentation. The validity of the data was tested using triangulation of sources, techniques, and time, with data analysis through the stages of reduction, presentation, and drawing conclusions. Results The research shows that: (1) The application of differentiated learning includes planning through mapping learning needs and implementing Integrate content, process, and product differentiation. (2) This approach is effective increase confidence and a deeper understanding of the material, reflected from improving learning outcomes. (3) The obstacles faced include limitations time management, media availability, consistency of classroom management, and mental load teacher. (4) The solutions implemented are the optimization of local media and collaboration between teachers through the Teacher Working Group (KKG).